Islamization of Human Sciences, 2nd ed. - Hussain, Mohd. Yusof (IIUM Press, 2009)
This book is a compilation of selected papers that have been presented in the International Conference on Islamization of Human Sciences organized by the Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia on 4th – 6th August 2000. The papers were selected for publication based on two criterias, i.e. they are related to Islamization of Human Sciences, they will enhance our knowledge on the purpose, goals, problems and work-plan for Islamization of knowledge. This book is compiled to help students understand Islamization of knowledge particularly Islamization of Human Sciences and to enable them to embark on the project of Islamization of Human Sciences with renewed vigour. The book is intended for those who have some background in Islamization of knowledge. Thus, while some terms and ideas in Islamization of knowledge are defined, familiarity with most terms on Islam and Islamization is assumed. It is hoped that this book will encourage and motivate more Islamic scholars to involve themselves in this noble effort of Islamization of Human Sciences.